Investigation of carbon nanotube ink with PDMS printing plate on fine solid lines printed by micro-flexographic printing method - Hassan, S; Yusof, M S; Ding, S; Maksud, M I; Nodin, M N; Mamat, K A; Sazali, M S; Rahim, M Z (IOP Publishing, 2017)
Micro-flexographic printing which is combination of flexography and micro-contact printing is a unique printing technique that create graphic, electronic and biomedical printed image on variable substrates. Therefore, an investigation for its potential usage in global area of printing hence a research for suitable ink and printing plate related to this process is vital. This paper will focus on investigating the printability of Carbon Nanotube (CNT) ink with polydimethylsiloxane (PDMS) printing plate. There are two types of CNTs ink which are solvent base and water base. A printing trial has been carried out in comparison with CNTs inks and PDMS printing plate with fine solid lines image on it to check the suitability of the printing plate development for micro-flexographic printing technique. The result shows that CNT water base ink is suitable with PDMS printing plate in printing fine solid lines image.